Design And Development of A Project-Based Learning (PJBL) LMS To Improve The Competence of Junior Network Administrators Among Grade XI Students at SMK Ketintang Surabaya - Firlin Ramadisha; Tiara Miranti; Adellya Puspita Ningrum; Rika Fitri Ramadani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Indonesia's low literacy achievement, reflected in its 68th ranking out of 81 countries in PISA 2022, underscores the urgency of developing alternative literacy programs beyond formal schooling. Although literacy research has been widely conducted in formal school settings, studies specifically examining literacy programs in non-formal institutions with inclusive reward systems in Indonesia remain scarce. This research gap motivated the present study, which aims to examine the role of literacy activities in fostering learning enthusiasm and creative capacity among learners at Yayasan Berbudi Luhur Indonesia. The foundation organizes afternoon learning programs for children from kindergarten to elementary school age, encompassing reading, storytelling, writing, and drawing activities, supported by a monthly reward system designed to encourage achievement motivation. A descriptive qualitative approach was employed, utilizing observation, in-depth interviews, and documentation. Participants comprised 30 learners, 5 tutors/facilitators, and foundation administrators. Findings indicate that consistent literacy programs combined with periodic rewards significantly increased learners' enthusiasm, evidenced by an average attendance rate of 87.3%, active participation, and improved quality of produced works. Creative capacity developed through short story writing, illustration drawing, and oral presentations, with a total of 524 works produced over three months. The monthly reward system functioned as an effective extrinsic motivator, progressively cultivating intrinsic motivation in 73% of learners.